Ovarian Strumal Carcinoid: Case Report, Systematic Literature Review and Pooled Analysis - Turla, Antonella; Zamparini, Manuel; Milione, Massimo; Grisanti, Salvatore; Amoroso, Vito; Pedersini, Rebecca; Cosentini, Deborah; Berruti, Alfredo (Frontiers in Endocrinology, 2022)
Abstract Background Ovarian strumal carcinoid is a rare tumor in which thyroid (struma) and carcinoid components coexist. The disease is generally considered to be a borderline malignancy, however, cases with metastatic disease have been described. No data in the literature are available to guide diagnosis and therapy. Methods We performed a pooled analysis and a systematic review of histopathological-confirmed strumal carcinoid cases published in the literature using the following keywords: “strumal carcinoid of the ovary”, “strumal carcinoid case report”. A case of strumal carcinoid tumor diagnosed and followed-up at the Medical Oncology Unit of Spedali Civili (Brescia, Italy) was also described and included. Results Sixty-six eligible publications were identified, providing data from one hundred and seventeen patients, plus a case diagnosed at our institution. At presentation, among the eighty-eight patients with symptomatic disease, 37% of patients suffered from abdominal distention and 49% from pain due to a growing abdominal tumor mass, 37% from constipation (peptide YY was analyzed in only nine of them, resulting above the physiologic range). Surgery was the primary therapy in 99% of the patients. Three patients had metastatic disease at diagnosis and five patients underwent recurrence after radical surgery. Histology at disease recurrence concerned the thyroid component in two patients, the carcinoid component in two patients, both histologies in one patient. Median disease-free survival and overall survival in this series were not attained. Conclusion Strumal carcinoid of the ovary generally presents a benign behavior and surgery is curative in most cases. However, a small group of patients with this disease can undergo disease recurrence due to both the thyroid and the neuroendocrine (carcinoid) components. A follow-up in radically operated patients is therefore needed, particularly in those with a voluminous disease at diagnosis.